SAT0504 Predictive ability of biomarkers linked with synovitis for future incidence of painful knee osteoarthritis in a community based cohort of middle-age women. (15th June 2017) - Thudium, CS; Kluzek, S; Newton, JL; Spector, T; Hart, D; Karsdal, MA; Bay-Jensen, AC; Arden, N
Abstract : Background: Radiographic knee osteoarthritis (RKOA) is associated with the knee pain. However, more than half of the middle-aged individuals with RKOA will report no concurrent knee pain. Specific matrix metalloproteinases (MMPs) generated protein fragments have been associated with knee synovitis and suggested as specific neo-epitope biomarkers of joint remodelling. Objectives: The aim of the study was to evaluate the association between MMP-derived neo-epitope biomarkers measured in serum, and future incidence of either painful RKOA or RKOA without pain, in a cohort of middle-aged women with no RKOA at baseline. Methods: 585 participants (mean age 53.2, mean BMI 25.1) from the Chingford 1000 Women Study Chingford Women Study had serum biomarker levels of MMP- degraded of CRP (CRPM), collagen type II (C2M) and collagen type III (C3M) measured at year 2 or 3 of the study. All participants had a Kellgren Lawrence (KL) score of 0 in both knees at baseline. Ten years following the recruitment, incidence of RKOA was determined as KL ≥2 and painful RKOA was defined as the presence of pain on any number of days in the preceding month in the knee with RKOA. Log-transformed normalised biomarker levels were utilised in separate logistic regression models adjusted for age. Outcomes were defined as either RKOA without pain or painful RKOA. Further analyses were performed adjusting for both age and BMI. Results: 24.6% of women developed RKOA during 10 years after the recruitment, but only 8.9% of developed RKOA associated with concurrent knee pain. After adjusting for age, statistically significant positive associations were found between C3M and CRPM and the risk of developing painful RKOA with odds ratio (OR) =3.4 (95% confidence interval (CI): 1.4 to 8.2), and OR=2.5 (95% CI: 1.2, 5.2) respectively. After adjusting for age and BMI, only C3M was positively associated with risk of developing painful RKOA with OR=3.2 (95% CI: 1.3, 7.8). Conclusions: In a population of middle-aged women without knee osteoarthritis, an MMP generated neo-epitope of collagen III previously linked with knee synovitis (C3M) can independently identify high-risk individuals for developing painful RKOA. These findings indicate that targeting MMP activity may be a promising therapeutic strategy in well-targeted populations. Disclosure of Interest: C. Thudium Employee of: Nordic Bioscience, S. Kluzek: None declared, J. Newton: None declared, T. Spector: None declared, D. Hart: None declared, M. Karsdal: None declared, A. Bay-Jensen: None declared, N. Arden: None declared